1998
DOI: 10.1109/27.700796
|View full text |Cite
|
Sign up to set email alerts
|

Experimental studies of overmoded relativistic backward-wave oscillators

Abstract: Internal field-emission breakdown in the electrodynamic structures of high-power microwave (HPM) devices can seriously limit the device's output power and pulse duration. Increasing the diameter of the electrodynamic structure to several times an electromagnetic wavelength can reduce these internal fields to below critical breakdown levels, but may introduce mode competition as an unwanted side effect. This paper presents the design and results of experiments with overmoded (D= 3), sinusoidally corrugated back… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…To overcome these problems, the overmoded structure is the best choice, though it was introduced for increasing the maximum handling power in microwave devices at first. [12][13][14] So an overmoded RSWO, one of typical Cerenkov devices, is adopted to generate 0.14 THz high power radiation in our design. The 0.14 THz RSWO with key structural parameters denoted is schematically shown in Fig.…”
Section: Design Of 014 Thz Overmoded Rswomentioning
confidence: 99%
“…To overcome these problems, the overmoded structure is the best choice, though it was introduced for increasing the maximum handling power in microwave devices at first. [12][13][14] So an overmoded RSWO, one of typical Cerenkov devices, is adopted to generate 0.14 THz high power radiation in our design. The 0.14 THz RSWO with key structural parameters denoted is schematically shown in Fig.…”
Section: Design Of 014 Thz Overmoded Rswomentioning
confidence: 99%
“…Many authors [1][2][3][4][5][6][7][8][9][10][11][12] have focused their attention on this device for more efficient operation at high-power levels, and important results have been obtained both experimentally and theoretically. In order to further enhance the output power of microwave and the conversion efficiency of electron beam to microwave radiation, some scientists [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] have introduced background plasmas into the BWOs, and both theoretical and experimental results have demonstrated that the background plasmas improve the beam-waveguide interaction dramatically.…”
Section: Introductionmentioning
confidence: 96%
“…The oversized approach has been successfully used to increase the power-handling capacities of slow-wave HPM devices. Important examples of overmoded devices are the multi-wave Cerenkov generator (MWCG) developed by Bugaev et al (1990a), the relativistic diffraction generator (RDG) developed by Bugaev et al (1990b), the relativistic backward-wave oscillator (RBWO) developed by Abe et al (1998), and the surface-wave microwave oscillator developed by Vlasov et al (2000). Although significant improvements have been achieved by using overmoded structures to reduce the internal reversed electric fields in HPM devices, there are still other issues that need to be investigated.…”
Section: Introductionmentioning
confidence: 98%